A cousin's promise - Brunstetter, Wanda E. (Brunstetter, Wanda E. Indiana cousins, 2009)
Crippled in a horrific accident, Wayne Lambright feels unable to care for himself, much less Loraine Miller, his future bride. Will he sacrifice his happiness to give Loraine a better life? When ex-boyfriend Jake Beecy returns, Loraine's heart is torn. Will she renew an old love or keep her promise to the new?